2011
DOI: 10.1352/1944-7558-116.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease Risks in Young Adults With Autism Spectrum Disorder: Forewarned Is Forearmed

Abstract: An emerging, cost-effective method to examine prevalent and future health risks of persons with disabilities is electronic health record (EHR) analysis. As an example, a case-control EHR analysis of adults with autism spectrum disorder receiving primary care through the Cleveland Clinic from 2005 to 2008 identified 108 adults with autism spectrum disorder. In this cohort, rates of chronic disease included 34.9% for obesity, 31.5% for hyperlipidemia, and 19.4% for hypertension. Compared with a control cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 42 publications
(35 reference statements)
3
95
1
4
Order By: Relevance
“…15,34, 35 Kohane and colleagues recently examined health conditions in children and young adults with ASD through several large quaternary hospitals and found a high prevalence of epilepsy, schizophrenia, and bowel disorders. 15 A similar review of electronic health records by Croen and colleagues found that young adults with ASD experience increased rates of seizures, hypertension, dyslipidemia, sleep disorders, and nearly all psychiatric disorders compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…15,34, 35 Kohane and colleagues recently examined health conditions in children and young adults with ASD through several large quaternary hospitals and found a high prevalence of epilepsy, schizophrenia, and bowel disorders. 15 A similar review of electronic health records by Croen and colleagues found that young adults with ASD experience increased rates of seizures, hypertension, dyslipidemia, sleep disorders, and nearly all psychiatric disorders compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…3 Prior studies have documented that people with disabilities face disparities in health and healthcare as compared to people without disabilities. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Though some studies assessing healthcare disparities for adults with developmental disabilities have included participants on the autism spectrum, with the exception of one small study using administrative data, 21 they do not report results separately for autistic participants. Most studies also primarily include participants with intellectual disabilities, and may not be generalizable to the full range of individuals now recognized as on the autism spectrum, a majority of whom do not have an intellectual disability.…”
mentioning
confidence: 99%
“…This may be due to genetic factors [10,11], psychopharmacological effects [12][13][14], and other risk factors for obesity (e.g., sleep problems, food selectivity, delayed/impaired motor development, and family functioning) [9]. However, methods to help prevent obesity among handicapped people remain unclear, as most studies have investigated the mechanisms of obesity in relation to health promotion among non-disables people.…”
Section: Introductionmentioning
confidence: 99%